Omega-3 fatty acids attenuate constitutive and insulin-induced CD36 expression through a suppression of PPARα/γ activity in microvascular endothelial cells - Madonna, Rosalinda; Salerni, Sara; Schiavone, Deborah; Glatz, Jan F.; Geng, Yong-Jian; Caterin, Raffaele De (Thrombosis and Haemostasis, 2011)
Microvascular dysfunction occurs in insulin resistance and/or hyperinsulinaemia. Enhanced uptake of free fatty acids (FFA) and oxidised low-density lipoproteins (oxLDL) may lead to oxidative stress and microvascular dysfunction interacting with CD36, a PPARα/γ-regulated scavenger receptor and long-chain FFA transporter. We investigated CD36 expression and CD36-mediated oxLDL uptake before and after insulin treatment in human dermal microvascular endothelial cells (HMVECs), ± different types of fatty acids (FA), including palmitic, oleic, linoleic, arachidonic, eicosapentaenoic (EPA), and docosahexaenoic (DHA) acids. Insulin (10−8 and 10−7 M) time-dependently increased DiI-oxLDL uptake and CD36 surface expression (by 30 ± 13%, p<0.05 vs. untreated control after 24 hours incubation), as assessed by ELISA and flow cytometry, an effect that was potentiated by the PI3-kinase inhibitor wortmannin and reverted by the ERK1/2 inhibitor PD98059 and the PPARα/γ antagonist GW9662. A ≥24 hour exposure to 50 μM DHA or EPA, but not other FA, blunted both the constitutive (by 23 ± 3% and 29 ± 2%, respectively, p<0.05 for both) and insulin-induced CD36 expressions (by 45 ± 27 % and 12 ± 3 %, respectively, p<0.05 for both), along with insulin-induced uptake of DiI-oxLDL and the downregulation of phosphorylated endothelial nitric oxide synthase (P-eNOS). At gel shift assays, DHA reverted insulin-induced basal and oxLDL-stimulated transactivation of PPRE and DNA binding of PPARα/γ and NF-κB. In conclusion, omega-3 fatty acids blunt the increased CD36 expression and activity promoted by high concentrations of insulin. Such mechanisms may be the basis for the use of omega-3 fatty acids in diabetic microvasculopathy.
Keywords: Insulin; atherosclerosis; CD36; omega-3 fatty acids; type 2 diabetes; insulin resistance